The Impact of Government Behaviors on the Transition Towards Carbon Neutrality in the Construction Industry: A Perspective of the Whole Life Cycle of Buildings - Tang, Daizhong; Gong, Xueyang; Liu, Menglan (Frontiers in Environmental Science, 2022)
The carbon-intensive economy has dramatically caused global climate changes and profoundly impacted humankind. As one of the largest energy consumers, carbon emissions in the construction industry (CECI) play a crucial role in achieving the carbon neutrality goal. Government behaviors could significantly affect CECI. However, few studies have comprehensively reviewed existing literature regarding the effect of government instruments on triggering carbon reduction. A total of 1,082 papers about CECI from 51 countries/regions were retrieved in this study, while 296 relevant articles on the government behaviors in CECI were collected to conduct further analysis. Based on the bibliometric analysis with CiteSpace, the co-occurrence networks of countries/regions, institutions, keywords and cluster analysis are applied to illustrate the characteristics of previous studies. Furthermore, a research framework has been formulated to review the impact of government behaviors on CECI during the life cycle of buildings. The result indicated that government behaviors could affect CECI through three stages, i.e., material production, construction and operation, which is considered the transmission path of government behaviors towards CECI. Moreover, the findings revealed that government behaviors present the most significant impact on CECI in the following sectors: 1) the green supply chain management and waste recycling in the material production stage; 2) the green building decisions and the adoption of off-site construction in the construction stage; 3) energy conservation behaviors and green retrofit decisions in the operation stage. Finally, this study discusses prior study gaps and provides potential directions for future research.